Merging Our Understanding of Anxiety and Exposure: Using Inhibitory Learning to Target Anxiety Sensitivity in Exposure Therapy. Issue 4 (July 2022) - Bautista, Chandra L.; Teng, Ellen J.
Exposure-based therapies are the gold standard treatment for anxiety disorders, and recent advancements in basic and clinical research point to the need to update the implementation of exposure. Recent research has highlighted the importance of transdiagnostic factors such as anxiety sensitivity (AS), or fear of anxiety-related sensations. Elevated AS is common among all anxiety disorders and contains three dimensions, or expectancies, that can be used to guide treatment. Recently, treatments directly targeting AS have shown potential in reducing symptoms of anxiety. In addition, inhibitory learning theory (ILT) provides an alternative explanation of exposure processes based on basic learning research. ILT extends the current framework by accounting for renewal of fear, which is important given the substantial number of individuals who experience a return of symptoms following treatment. The current paper will provide an overview of ILT and discuss several ILT techniques that can be used to target AS. These two converging bodies of research hold strong potential for optimizing treatment for anxiety.